РЕЗУЛЬТАТЫ СКРИНИНГА РЕГУЛЯРНОСТИ ЭВАКУАТОРНОЙ ФУНКЦИИ КИШЕЧНИКА У УЧАЩИХСЯ ВУЗОВ - Дробишевска, А О; Стадник, Д П; Церцеил, В В; Кушнир, П А; Тен, Н С; Ишанкулыева, С Ш; Эминова, Г Д; Розметбаева, Ш Р; Акимов, А А (FORCIPE, 2021)